The political economy of American trade policy - Krueger, Anne O. (National Bureau of Economic Research project report., 1996)
Exploring the political and economic determinants of trade protection, this study provides a wealth of information on key American industries and documents the process of seeking and conferring protection. Eight analytical histories of the automobile, steel, semiconductor, lumber, wheat, and textile and apparel industries demonstrate that trade barriers rarely have unequivocal benefits and may be counterproductive. They show that criteria for awarding protection do not take into account the interests of consumers or other industries and that political influence and an organized lobby are major sources of protection. Based on these findings, a final essay suggests that current policy fails to consider adequately economic efficiency, the public good, and indirect negative effects. This volume will interest scholars in economics, business, and public policy who deal with trade issues.